2013
DOI: 10.1371/journal.pone.0067866
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hepatitis B Virus Vaccination Has Reduced Hepatitis B Virus Transmission in The Netherlands

Abstract: Background & AimsIn the Netherlands, a selective hepatitis B virus (HBV) vaccination programme started in 2002 for men having sex with men, drug users, commercial sex workers and heterosexuals with frequent partner changes. We assessed the programme's effectiveness to guide policy on HBV prevention.MethodsWe analysed reports of acute HBV infection in the Netherlands between 2004 and 2010 requesting serum from patients for HBV-genome S- and C-region sequencing. We used coalescence analyses to assess genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…112 However, a follow-up study with increased sample size (n=894, versus n=85) suggested that reduced HBV transmission was in fact due to reduced incidence in MSM, highlighting the importance of sample size and extended sampling periods for studies of this type. 113 Alternatively, gene sequence data can be used to reconstruct HIV transmission networks rather than phylogenies, and cluster size distributions (CSD) can be compared over the course of a prevention trial or intervention. 59,114,115 In theory, CSDs will be dominated by larger clusters in populations where epidemic drivers (individuals with relatively high infectiousness) persist.…”
Section: Phylogenetics and Transmission Dynamics In Generalized Epidementioning
confidence: 99%
“…112 However, a follow-up study with increased sample size (n=894, versus n=85) suggested that reduced HBV transmission was in fact due to reduced incidence in MSM, highlighting the importance of sample size and extended sampling periods for studies of this type. 113 Alternatively, gene sequence data can be used to reconstruct HIV transmission networks rather than phylogenies, and cluster size distributions (CSD) can be compared over the course of a prevention trial or intervention. 59,114,115 In theory, CSDs will be dominated by larger clusters in populations where epidemic drivers (individuals with relatively high infectiousness) persist.…”
Section: Phylogenetics and Transmission Dynamics In Generalized Epidementioning
confidence: 99%
“…However, regional prevalence of HBV is highly variable [1] and the Netherlands is a low endemic country, with an estimated incidence of 1.2 acute HBV-infections/100,000 inhabitants in 2010 [2], and 0.2 percent of the population having chronic HBV-infections [3].…”
Section: Introductionmentioning
confidence: 99%
“…[84][85] Moreover, a very good field for reducing the HBV burden through the HBV vaccination is concerning men who have sex with men, and Commercial sex workers, among which there exist a disproportionate burden of HBV infections. [86][87][88][89][90][91][92][93][94][95] The WHO recommendations include the offer the rapid HBV vaccination regimen for persons who inject drugs. [96][97] As far as concerns one of the strengths of this review, a gap has been filled, since it was shown the use of economic evaluations in highly endemic areas, that was lacking in previous reviews, 11 and this is very important to raise both public awareness of the effectiveness and economic attractiveness of universal immunization against HBV.…”
Section: Discussionmentioning
confidence: 99%